Direction, Panel Height, and Tapping Frequency Affect The Daily Bark Consumption in Hevea Rubber Tapping - Junaidi, Junaidi; Atminingsih, Atminingsih; Darojat, Muhammad Rizqi (Universitas Muhammadiyah Yogyakarta, 2019)
Bark consumption is defined as the thickness of sliced bark per time unit. This research, aiming to identify the effects of direction, panel height, and tapping frequency on daily bark consumption, was carried out at Sungei Putih Research Center, North Sumatera and several estates in Lampung (Kedaton, Bergen, and Way Lima) from January to March 2018. The observations involved 15 tapping tasks consisting of GT 1, PB 260, and mixed clones. Bark samples were collected from 10 randomized trees in each task. Tapping direction was distinguished as downward tapping and upward tapping, while panel height was classified into 50 cm, 50 – 100 cm, and 100 – 130 cm in downward tapping and 130 – 150 cm, 150 – 170 cm, and 170 cm in upward tapping. Tapping frequency effect was investigated in a trial plot using frequency of once in three days (d3), once in four days (d4), once in five days (d5), once in six days (d6), and once in eight days (d8) on the basal panel (B0-2). Bark consumption was measured directly using a digital caliper. The observation result indicated that upward tapping had higher bark consumption than downward tapping. In downward tapping, the lower tapping position, the higher bark consumption would be, whilst in upward tapping, bark consumption increased along with the panel height. Low tapping frequency (d4, d5, d6, and d8) showed higher bark consumption per tapping than d3, yet they had lower cumulative bark consumption per year.